1987
DOI: 10.1111/j.1600-051x.1987.tb01521.x
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile periodontitis: an epidemiological study in the west Midlands of the United Kingdom

Abstract: The prevalence of juvenile periodontitis was studied in a sample of 7266 school children in the cities of Coventry and Birmingham. The subjects were aged 15 to 19 years, and represented the range of different ethnic groups seen in the population of the West Midlands. A two-stage diagnostic procedure was used, whereby subjects were screened initially by assessment of probing depths around the incisors and first molars. Positive subjects were then diagnosed definitively by full clinical and radiographic examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
2
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 26 publications
3
41
2
3
Order By: Relevance
“…In our study, gender did not influence the radiographic CEJ‐AC distance significantly. This is in accordance with other studies that found no association between gender and the prevalence of periodontal disease 4,19‐21 …”
Section: Discussionsupporting
confidence: 93%
“…In our study, gender did not influence the radiographic CEJ‐AC distance significantly. This is in accordance with other studies that found no association between gender and the prevalence of periodontal disease 4,19‐21 …”
Section: Discussionsupporting
confidence: 93%
“…As various studies we found that periodontitis disease is usually more common in females than males (26)(27)(28). However, several other studies have noted different gender distributions (29,30). The fact that there is a majority of women may be due in part to hormonal exchange during the menstrual cycle and pregnancy which may consequently worsen the clinical course of this disease (26).…”
Section: Discussionmentioning
confidence: 86%
“…From 2,924 retrieved studies, 51 remained for assessment. At extraction data stage, we excluded 18 more studies because of absence or too restrictive diagnostic criteria (Aass, Albander, Assenden, Tollefsen, & Gjermo, ; Belhaissi, Cherkaoui, Laporte, & Miquel, ; Cappelli, Ebersole, & Kornman, ; Gjermo, Bellini, Santos, Martins, & Ferracyoli, ; Kumar, Altamash, & Qamruddin, ; Van der Velden et al, ; Wagaiyu & Wagaiyu, ; Yoshida, Fujiwara, Ooshima, & Sobue, ) or due to a duplicate study (Saxby, ) or a study reporting data from previous studies (Oliver, Brown, & Löe, ). We also excluded three studies having an inadequate study design (Fatema & Desai, ; Nassar, Afifi, & Deprez, ; Rhee, Sekhon, & Boehm, ) and one more study with no reported global prevalence (Albandar, Brown, & Löe, ).…”
Section: Resultsmentioning
confidence: 99%